A STUDY OF COMMUNITY PARTICIPATIONIN SOLID WASTE MANAGEMENT IN KATHMANDU METROPOLITAN CITY - Dahal, Indra Prasad (IJRDO - Journal of Applied Management Science, 2017)
Solid waste management in Nepal has been one of the important and seriously discussed topics. Kathmandu Metropolitan City is unable to handle the solid waste by itself. So, community participation is being encouraged to manage the waste. In this way, my study will focus on community participation in solid waste management in Kathmandu. There are varieties of study areas for my research, Old Newar settlement (Ashan and Jyatha),Thamel (Tourism area), and Samakhuhsi Town Planning (ward no:-29 out of 38 wards of Kathmandu Metropolitan City.) Waste management in those areas has been managed through Ngos and Private sectors, communities, and Metropolitan Authority. Household questionnaire and interviews will be used as the research tools and a total of 48 respondents and 11 key respondents (2/2 senior employees ) from community organizations including 3 staffs from environment department of Kathmandu Metropolitan City respondents interviewed around the study areas. The study will use both qualitative and quantitative approach to analyze the information. It is believed that about 75% of the total waste generated in Kathmandu is of organic type which can be composted. The main aim of Solid Waste Management Practice is seen in all these settlements to segregate waste at source. All the communities have different approaches which the people follow in segregating waste. In all the settlements bins are provided. At Ashan and Local Newar Settlement area has a central collection system but the community members are asked to segregate waste. In Thamel too, it is a similar case but a private company is involved (directly) in managing waste. In Samakhushi Town Planning area, people are encouraged to manage waste in individual level in their own household. This Study will try to depict the status of solid waste management practices as well as the status of community participation community members in other activities such as recyclingreuse, disposal of waste, decision making within entire ward no 29 out of 38 wards of Kathmandu Metropolitan City